Sexual harassment in Islamic Sharia (A critical study of relevant legal articles in Iraqi law) - Falah Abdul Hassan Hashem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The subject of the research is sexual harassment and an attempt to identify its provision in Islamic Sharia, whether jurisprudential or penal, while criticizing the articles that the Iraqi legislator has allocated to sexual harassment. The importance of the research is to strengthen the law and try to find legal formulas that will deter the act of harassment in the present time in which it has developed. The images of harassment varied. The research problem: the development of cases of harassment in society, and it has become a phenomenon, and there is an absence of knowledge regarding this topic. The most important results of the research: harassment is forbidden in Islamic Sharia according to various evidences, and that the political ruler can legislate a penal law that achieves deterrence and leads to the spread of safety and stability in society. The Iraqi law regarding harassment needs amendments and reforms to make it achieve deterrence and societal stability.